446 A qualitative exploration using focus groups, of the perceived barriers and enablers of hospital pharmacists to participating in simulation based training. (13th April 2023) - Lea, N; Lloyd, M; Bennett, N
Abstract: Introduction: The role of hospital pharmacists has changed significantly over the past decade with a need for further educational interventions to support their professional development. Simulation based training (SBT) is widely used by other healthcare professionals to enhance skill acquisition and performance (1). However, the use of SBT does not appear to have evolved to the same level for hospital pharmacists (1), and there is no evidence exploring their experiences of participating in SBT and the barriers and enablers towards engaging with this training modality. Aim: To explore the experiences and perceptions of hospital pharmacists of SBT, and to identify perceived barriers and enablers of participating in SBT. Methods: This was a descriptive qualitative case study. A purposive sample of trainee and qualified pharmacists from a large acute teaching hospital were invited to participate in a focus group discussion. A topic guide was utilised to guide discussions, with topics such as previous SBT experience, barriers to participation within SBT and how they feel SBT would impact on their clinical practice. The focus groups were conducted within a private room, recorded, and transcribed verbatim, then analysed thematically using COM-B (capability, opportunity, motivation, behaviour) (2) as an analytical framework. Relevant approvals were obtained prior to commencing the research. Results: Seventeen participants were recruited into one of four focus groups, with allocation based on Agenda for Change banding (band 5 to 8A). Focus groups lasted 45-60 minutes. Ten themes were identified and mapped across the COM-B domains with contrasting differences reported depending on participant experience and seniority. Psychological capability (knowledge and understanding of SBT, clinical knowledge and skills), physical opportunity (workload and time pressures, infrastructure to support SBT), social opportunity (social expectations of pharmacists, culture of learning within pharmacy), automatic motivation (emotional factors, desires for professional development), and reflective motivation (perceptions of SBT, belief in own role and abilities) were all factors reported as influencing their participation with SBT in hospital settings. All groups expressed that SBT is mainly focused on clinicians with limited pharmacist involvement as an 'add on'. Pharmacists reported a lack of confidence in SBT, with limited opportunities for involvement within the hospital setting, and concerns on their ability to communicate with other healthcare professionals during any SBT. Conclusion: This is the first known study exploring the experiences of SBT amongst hospital pharmacists. There is a desire to participate in SBT, however it is clear, that significant interventions and further training on SBT modalities are required to enable this, including opportunities to participate in contextualised SBT, reflecting the role, expectations, and professional developmental needs of pharmacists. Clear leadership and signposting are needed to operationalise this and reap the benefits of SBT. These results can be utilised as a framework to support the design and implementation of a successful SBT programme for hospital pharmacists as part of intra-professional and multi-professional SBT programmes. This study is limited as a single-site case study and further investigation is required to explore further views of the hospital pharmacist workforce. References: 1. Lloyd M, Watmough SD, Bennett N. Simulation based training and its application in clinical pharmacy. Clinical Pharmacist 2018;10:(9)3-10 doi:10.1211/CP.2018.20205302 2. Michie S, van Stralen M.M, West R. The behaviour change wheel: A new method for characterising and designing behaviour change interventions. Implementation Science 2011; 6: 42.